Manajemen Sumber Daya Manusia Dalam Administrasi Kesehatan Sekolah Dasar - Surya Utama; Alisarjuni Padang (STIKES Columbia Asia Medan, 2025)
The aim of the research is to determine the human resource management of the MIS Insan Ikhlas Islamic School Medan Elementary School. The type of research is qualitative with a qualitative descriptive approach. Data collection techniques use documentation, interviews and observation. Data analysis is carried out by organizing data, describing it into units, synthesizing it, arranging it into patterns, choosing what is important and what will be studied, and making conclusions that can be shared with others. There are three stages in data analysis, namely data reduction, data presentation, and verification. Research results: 1) Job description of human resource management for MIS Insan Ikhlas Islamic School, including: Principal as Educator, manager, administrator, supervisor, leader , innovator, and motivator; 2) Efforts to increase human resource competency; 3) Control of the human resources of MIS Insan Ikhlas Islamic School, both from the school, the management/foundation and the Education Department in order to improve the competency of elementary school teachers, including starting from the recruitment stage of qualified teaching staff candidates, providing personal coaching to teachers who experience difficulties during the learning process.